2009
DOI: 10.1088/0004-637x/692/2/1125
|View full text |Cite
|
Sign up to set email alerts
|

OBSERVATIONS OF THE HELIOSHEATH AND SOLAR WIND NEAR THE TERMINATION SHOCK BYVOYAGER 2

Abstract: This paper describes the principal features of 24 hr averages of the magnetic field strength variations B(t) and their relationships to the plasma and energetic particles observed prior to and after the crossing of the termination shock (TS) by Voyager 2 (V2). The solar wind (pre-TS crossing) and heliosheath (post-TS crossing) data extend from day of year (DOY) 1 through 241, 2007 and from 2007 DOY 245 through 2008 DOY 80, respectively. In the solar wind, two merged interaction regions (MIRs) were observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 33 publications
(50 reference statements)
1
36
0
2
Order By: Relevance
“…It is surprising that V1 observed a large oscillation of B during this interval. Large fluctuations in B were also observed in unipolar regions by V1 from 2004V1 from .98 to 2005V1 from .3 [Burlaga et al, 2006 and by V2 from 2008.11 to 2008.56 [Burlaga et al, 2009a]. It will be interesting to determine whether V2 will observe large fluctuations in B when it becomes immersed in the unipolar magnetic fields from the southern polar coronal hole.…”
Section: Polarity and Strength Of The Magnetic Fieldmentioning
confidence: 97%
See 1 more Smart Citation
“…It is surprising that V1 observed a large oscillation of B during this interval. Large fluctuations in B were also observed in unipolar regions by V1 from 2004V1 from .98 to 2005V1 from .3 [Burlaga et al, 2006 and by V2 from 2008.11 to 2008.56 [Burlaga et al, 2009a]. It will be interesting to determine whether V2 will observe large fluctuations in B when it becomes immersed in the unipolar magnetic fields from the southern polar coronal hole.…”
Section: Polarity and Strength Of The Magnetic Fieldmentioning
confidence: 97%
“…[19] Magnetic pressure P B = (B 2 /8p), solar wind thermal pressure P P = NkT, total pressure P BP = (P B + P P ), and b = P P /P B in the solar wind ahead of the termination shock (TS) and in heliosheath behind the TS (from DOY 245, 2007to DOY 75, 2008 are discussed by Burlaga et al [2009a]. In the heliosheath from DOY 1 − 75, 2008 they reported that P BP = 14.1 × 10 −14 dyn cm −2 , and b = 1.1.…”
Section: Pressures and Betamentioning
confidence: 99%
“…What is different is the modeled total pressure, which is higher at the poles than downwind, leading to an IHS that is about 30% thinner at the poles than their 220 au value. However, Galli et al (2016) base their poleward pressure on the flow speed observed by Voyager 2 in the heliosheath, 140 km s −1 , which originated as aslow SW (∼400 km s −1 ) prior to the TS (Burlaga et al 2009). We argue that this is not appropriate for the poles over most of the solar cycle where the heliosheath flow speed should be considerably higher.…”
Section: Correlation Of 1 Au Dynamic Pressure With Ena-derived Plasmamentioning
confidence: 99%
“…Based on a survey of outer heliospheric models (e.g., Pogorelov et al 2007Pogorelov et al , 2013Izmodenov et al 2009;Opher et al 2009Opher et al , 2015, a proton outbound along the heliographic equator will travel roughly an additional 200 au through the IHS to the pole as compared to a proton traveling directly poleward. For a flow speed in the IHS of ∼150 km s −1 (based on Voyager 2 observations; Burlaga et al 2009), this corresponds to a travel time difference of ∼6.5 years, or more than half a solar cycle. Thus even if the individual streamlines retain memory of their preshock solar wind conditions, ENAs observed along a polar-directed LOS will reflect SW variability averaged over half a solar cycle.…”
Section: Propagation Of Variations Along Streamlinesmentioning
confidence: 99%
“…After crossing of the termination shock, the Voyagers continue observing the sector structure (Burlaga et al 2006(Burlaga et al , 2007(Burlaga et al , 2009, implying that the HCS extends into the inner heliosheath. With the distance from the termination shock increasing and the distance to the heliopause going down, the plasma flow deviates more and more from the radial flow (Richardson et al 2009).…”
Section: Introductionmentioning
confidence: 99%